Use of nanobots in the liiving creature body condition diagnostics - I. Parkhomay; O. Parkhomay; Y. Bondar (Adaptivni Sistemi Avtomatičnogo Upravlinnâ, 2020)
The use of nanobots in the field of diagnosis is strictly related to the prohibition of cell damage during its disembarkation or removal from the body. Appropriate size requirements can be achieved only by molecule or small molecular complex that can be used for functions diagnostics in a living system. Such functions can be done only with presence of an energy source. Furthermore, this function is accompanied by energy dissipation. The relevance of the proposed study is due to the need for rapid and, importantly, accurate living creature body condition diagnostics. The proposed topic combines two aspects: purely technical (functioning of nanobots) and biological - the condition of the body. These aspects are themselves important enough scientific problems and their combination requires the creation of a technical and biological concept of diagnostics without damaging the functions of the living organism and its cells. In this paper, we propose a technique for applying nanoscale robotic systems toward the specific place, which diagnostics need them to be.